Yearbook of the European Convention on Human Rights/Annuaire de la convention europeenne des droits de l'homme, Volume 1 (1958) (Human Rights and Humanitarian Law - Book Archive pre-2000., 1959)
Old Title: "European Commission of Human Rights/Commission Europeenne des droits de l'homme: Ducuments and/et Decisions 1955 - 1956 - 1957".